2013
DOI: 10.1136/annrheumdis-2013-eular.2081
|View full text |Cite
|
Sign up to set email alerts
|

SAT0356 The Therapeutic Efficacy of the Novel Uricosuric Agent UR-1102 for Hyperuricemia and Gout

Abstract: Background Control of blood uric acid is important for the treatment of gout. The clinical potential of a selective uric acid transporter 1 (URAT1) inhibitor as a drug for hyperuricemia and gout remains unknown because currently available uricosuric drugs block renal uric acid reabsorption by inhibiting not only URAT1 but also other transporters responsible for renal tubular uric acid secretion, such as OAT1 or OAT3. We have identified a highly selective URAT1 inhibitor, UR-1102, which is now under clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…UR-1102 is a novel, URAT1, OAT1 and OAT3 inhibitor, that has shown a higher potency that benzbromarone in in vitro studies [Ahn et al 2013]. At the moment, no further studies or results have been reported regarding the development of this agent.…”
Section: Arhalofenate (Mbx-102)mentioning
confidence: 99%
“…UR-1102 is a novel, URAT1, OAT1 and OAT3 inhibitor, that has shown a higher potency that benzbromarone in in vitro studies [Ahn et al 2013]. At the moment, no further studies or results have been reported regarding the development of this agent.…”
Section: Arhalofenate (Mbx-102)mentioning
confidence: 99%
“…Epaminurad is a SURI (JW Pharmaceuticals, Seoul, South Korea). In vitro and animal studies demonstrated superiority in lowering SUA and increasing fractional excretion of uric acid compared to benzbromarone ( Ahn et al, 2013 ; Ahn et al, 2016 ). Epaminurad doses ranging from 1 to 10 mg were well-tolerated and achieved sustained dose-dependent urate-lowering effects ( Lee et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In In-vitro studies, UR-1102 exhibited selective inhibition of URAT1 transporter [89]. No studies have reported results on safety or efficacy.…”
Section: Ur-1102mentioning
confidence: 98%